Offshoring tasks, yet creating jobs? - Wilhelm Kohler; Jens Wrona (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
The policy debate views offshoring as job destruction. Theoretical models of offshoring mostly assume full employment. We develop a model of task trade that allows for equilibrium unemployment. In this model, there are two margins of adjustment. At the extensive margin, moving tasks offshore destroys jobs. At the intensive margin, due to higher productivity of labor in domestic tasks it creates jobs. Exploring these conditions in detail, we identify the potential of non-monotonic adjustment: Early stages of offshoring always lead to higher unemployment, while later stages may entail net job creation. We highlight this potential through numerical simulations.
urn:nbn:de:bsz:21-opus-56836
Keywords: F16; F11; 330; Offshoring; Trade in Tasks; Unemployment; Non-monotonicity; Offshoring; Globalisierung; Produktivität; Beschäftigungseffekt; Komparativer Kostenvorteil; Arbeitslosigkeit; Matching; Theorie